2010
DOI: 10.1097/anc.0b013e3181dd6dea
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Infants' Sympathetic Arousal and Associated Behavioral Responses to Sound Stimuli in the Neonatal Intensive Care Unit

Abstract: SC provides a noninvasive, sensitive measure of sympathetic arousal that may not be apparent in behavioral cues or states, or determined by standard physiological responses alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 33 publications
3
25
0
1
Order By: Relevance
“…The nature of the primary physiological responses (increased HR and decreased RR and oxygen saturation) and their timing (rapid onset during the 20 s after SP) suggest (i) a reflexive reaction, mediated by the brain stem, as shown for fetal cardiac reactivity to sounds and (ii) a stress (defensive) response, similar to those recorded for higher SPL stimuli (8,9,13,26) and further emphasized by the emotional sweating that reflects sympathetic nervous system responses to a stressor after SPs in the same SPLs (14). To measure the impact of these stimuli on cerebral oxygenation, we used an near-infrared spectroscopy (NIRS) technique that can evaluate regional cortical activation (reflected by an increase in oxygen consumption accompanying neuronal activation) after sensory stimuli and has been used after auditory stimuli (27,28).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The nature of the primary physiological responses (increased HR and decreased RR and oxygen saturation) and their timing (rapid onset during the 20 s after SP) suggest (i) a reflexive reaction, mediated by the brain stem, as shown for fetal cardiac reactivity to sounds and (ii) a stress (defensive) response, similar to those recorded for higher SPL stimuli (8,9,13,26) and further emphasized by the emotional sweating that reflects sympathetic nervous system responses to a stressor after SPs in the same SPLs (14). To measure the impact of these stimuli on cerebral oxygenation, we used an near-infrared spectroscopy (NIRS) technique that can evaluate regional cortical activation (reflected by an increase in oxygen consumption accompanying neuronal activation) after sensory stimuli and has been used after auditory stimuli (27,28).…”
Section: Discussionmentioning
confidence: 88%
“…One, which involved eight extremely-low-birth-weight infants, found no correlation between moderate NICU noise levels (50-60 dBA) and arterial blood pressure, although there were HR changes starting from 25 to 45 s after noise peaks (13). The second study found that 11 VPIs exhibited sympathetic arousal, as measured by skin conductance, in response to natural sound >65 dBA and with background noise <55 dBA (14). These studies, however, did not determine the differential auditory SPL sensitivity (signal-to-noise ratio, SNR) or the precise effects of acoustic changes (in response to SPL <70 dBA Leq) on the physiological well-being of these VPIs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SCA index monitors pain from heel stick [41]. The stress from tactile stimulation and stress from high decibel levels is monitored by SCA more sensitively and specifically than behavioral-state observations [14,15 ]. The SCA can assess pain from 25 weeks of gestational age [63] and could be a useful tool to monitor pain and discomfort in these patients.…”
Section: Clinical Applications For the Skin Conductance Algesimetermentioning
confidence: 99%
“…It has recently been described in infants of 22e27 weeks gestation and at different postnatal age (Munsters et al, 2009). Babies <28 weeks showed a maturational development of the skin conductance response and it was possible to differentiate between pain and discomfort but the authors recommended further studies to explore this aspect with more sensitive observational scores Abundant tactile stimulation as in excessive handling and exposure to noise in neonatal unit gave rise to stress levels similar to heel stick responses on SCA and plasma catecholamine levels (Salavitabar et al, 2008). SCA appears to be reliable in haemodynamically unstable patients and SCA responses to noxious stimuli are reliably attenuated by the use of analgesic agents.…”
mentioning
confidence: 91%